2021
DOI: 10.3390/foods10061282
|View full text |Cite
|
Sign up to set email alerts
|

Bee Pollen Diet Alters the Bacterial Flora and Antimicrobial Peptides in the Oral Cavities of Mice

Abstract: Background: Bee pollen (BP) has a broad range of beneficial effects on health. The aim of this study was to examine the effect of BP on the oral environment, including the microbiome and antimicrobial peptides. Methods: C57BL/6J mice were randomly divided into two groups: control and BP. The BP group was fed with a 5% BP diet for 1 month. Swabs from the oral and buccal mucosa and samples of the intestinal stool were collected. Genomic DNA was extracted and the microbiome was analyzed via 16S rRNA sequencing. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the oral cavity, BP fed at a ratio of 5% to rats for one month resulted in a marked increase in the genus Lactococcus ( Lactococcus lactis is known to prevent oral pathogen spread such as Streptococcus mutans and Porphyromonas gingivalis ) in oral and intestinal flora [ 218 ]. This effect in the oral cavity may not be totally due to the antimicrobial activity of BP, because the authors demonstrated that the latter did not have significant effect on Streptococcus mutans although a potent inhibitory effect was observed on Porphyromonas gingivalis, while an upregulated antimicrobial peptide production by oral epithelium was also noted.…”
Section: Resultsmentioning
confidence: 99%
“…In the oral cavity, BP fed at a ratio of 5% to rats for one month resulted in a marked increase in the genus Lactococcus ( Lactococcus lactis is known to prevent oral pathogen spread such as Streptococcus mutans and Porphyromonas gingivalis ) in oral and intestinal flora [ 218 ]. This effect in the oral cavity may not be totally due to the antimicrobial activity of BP, because the authors demonstrated that the latter did not have significant effect on Streptococcus mutans although a potent inhibitory effect was observed on Porphyromonas gingivalis, while an upregulated antimicrobial peptide production by oral epithelium was also noted.…”
Section: Resultsmentioning
confidence: 99%
“…Male C57BL/6 mice (eight-week-old) were obtained from Shanghai Slac Laboratory Animal Co., Ltd (Shanghai, China) and were used after acclimation for seven days. 17 All animal procedures were performed in accordance with the Guidelines for Care and Use of Laboratory Animals of Zhejiang University and approved by the Experimental Animal Welfare Ethics Committee of Zhejiang University. All mice were randomly distributed into eight groups ( n = 8); the corresponding treatments are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It has been concluded that BP can delay aging, improve the cardiovascular system, maintain the digestive system, prevent prostate degeneration, and enhance immunity according to a previously published article ( 76 , 83 ). In the apitherapeutic treatment, BP is used because it shows medicinal activities such as antimicrobial, antibiotic, anti-inflammatory, antiviral, analgesic, immunostimulant ( 84–86 ), anti-radiation, anti-tyrosinase, hepatoprotective, and antioxidant ( 22 , 87–89 ) ( Figures 1 , 2 ).…”
Section: Apitherapymentioning
confidence: 99%